Pengaruh pemberian ekstrak propolis secara aplikasi lokal pada proses pembentukan serabut kolagen pascapencabutan gigi marmot (cavia cobaya)= The Effects of Local Application of Propolis Extract on the Formatton of .. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Propolis is natural substance produced by bees. It has the potential of being antimicrobial, antiallergic, antifungal, and anti-inflammatory. Fla-vonoid and ferulic acid are propolis component which is function to promote wound healing. The aim of this research is to investigate the effect of the local application of propolis extract on the density of the collagen fibers amount in the healing process of wounds. The research sample consisted of 18 male guinea-pigs (Cavia cobaya) averaging 3 months of age. They were divided into 2 groups. The first group was the control group, which did not receive an application of propolis extract. The second group was treatment group, which received application of propolis extract on socket wounds after tooth extraction with a dosage of 400mg/kg of body weight. Histological observations of each group were conducted on the third, fifth and seventh days after extraction. The histological evaluation was based on the density of collagen fibers. The data was then analyzed using a nonparametic statistical test. The results of the research indicate that there are significant differences in the density of collagen fibers between the control group and the treatment group as shown by the observations made on the third, fifth and seventh days(p